Errors in the Measurement of Center of Pressure (CoP) Computed with Force Plate Affect on 3D Lower Limb Joint Moment During Gait - Kim, Heung-Youl; Ahn, Jae-Han; Sakurai, Shinji (International Journal of Sport and Health Science, 2007)
The purpose of this study was to investigate the effect of errors in the center of pressure (CoP) locations on three-dimensional (3D) lower limb joint moments during the stance phase of gait. Kinematic and kinetic data were collected from walking trials of one healthy male subject (age: 22yr, height: 181cm, body mass: 80kg). Changes of 3D joint moment were calculated using inverse dynamics with 3D video analysis and ground reaction force (GRF) measurement. Thereafter, the location of the CoP was shifted toward the antero-posterior/medio-lateral direction by ±10mm, ±20mm and ±30mm, respectively, and 3D joint moments were recalculated with the shifted CoP data. As a result of the simulated shift of the CoP in the antero-posterior direction, changes of magnitude in the ankle (dorsiflexion-plantarflexion), knee (flexion-extension), and hip joint moments (flexion-extension) were observed, while the moment patterns did not change. Simulated CoP shift in the medio-lateral direction altered the magnitude of the hip joint moment (abduction-adduction, internal-external rotation). Moreover it greatly affected the change of the inversion-eversion ankle joint moment. A shift of ±10mm of CoP in the medio-lateral direction reversed joint moment pattern of ankle joint inversion-eversion. The joint moment magnitudes and patterns were more sensitive to errors in the medio-lateral direction than in the antero-posterior direction, largely due to differences in the moment arm length and the direction of the GRF. This clearly illustrates the need to accurately determine CoP position in the calculation of lower limb joint kinetics.